Concentrations and sources of non-methane hydrocarbons (NMHCs) from 2005 to 2013 in Hong Kong: A multi-year real-time data analysis. (February 2015) - Ou, Jiamin; Guo, Hai; Zheng, Junyu; Cheung, Kalam; Louie, Peter K.K.; Ling, Zhenhao; Wang, Dawei
Abstract: To understand the long-term variations of nonmethane hydrocarbons (NMHCs) and their emission sources, real-time speciated NMHCs have been monitored in Hong Kong since 2005. Data analysis showed that the concentrations of C3 –C5 and C6 –C7 alkanes slightly increased from 2005 to 2013 at a rate of 0.0015 and 0.0005 μg m −3  yr −1 ( p  < 0.05), respectively, while aromatics decreased at a rate of 0.006 μg m −3  yr −1 ( p  < 0.05). Positive Matrix Factorization (PMF) model was applied to identify and quantify the NMHC sources. Vehicular exhaust, gasoline evaporation and liquefied petroleum gas (LPG) usage, consumer product and printing, architectural paints, and biogenic emissions were identified and on average accounted for 20.2 ± 6.2%, 25.4 ± 6.3%, 32.6 ± 5.8%, 21.5 ± 4.5%, and 3.3 ± 1.5% of the ambient NMHC concentrations, respectively. From 2005 to 2013, the contributions of both traffic-related sources and solvent-related sources showed no significant changes, different from the trends in emission inventory. On O3 episode days dominated by local air masses, the increase ratio of NMHC species from non-episode to episode days was found to be a natural function of the reactivity of NMHC species, suggesting that photochemical reaction would significantly change the NMHCs composition between emission sources and the receptors. Effect of photochemical reaction loss on receptor-oriented source apportionment analysis needs to be quantified in order to identify the NMHCs emission sources on O3 episode days. Highlights: Concentrations of C3 –C5 and C6 –C7 alkanes slightly increased from 2005 to 2013. Aromatics decreased at a rate of 0.006 μg m −3  yr −1 ( p  < 0.05). Contributions of both traffic-related sources and solvent-related sources showed no significant changes. Photochemical reaction significantly changed the NMHCs composition.